Step-by-step explanation:
x²-11x+32=4
x²-11x+28=0
(x-4)(x-7)=0
x=4 or x=7
_______
x²+8x-5=4
x²+8x-9=0
(x+9)(x-1)=0
x=-9 or x=1
_______
x²+x+4=5x+1
x²-4x+3=0
(x-1)(x-3)=0
x=1 or x=3
________
x²+x-24=-8x-2
x²+9x-22=0
(x+11)(x-2)=0
x=-11 or x=2
Answer:
1 .4x2-9= 2x+3,2x-3
2 .16x2-1=4x-1,4x+1
3 .16x2-4=4(2x+1)(2x-1)
4 .4x2-1=(2x+1)(2x-1)
Step-by-step explanation:
16x² − 1 = (4x − 1)(4x + 1) ; 16x² − 4 = 4(2x + 1)(2x − 1); 4x² − 1 = (2x + 1)(2x − 1) ;
4x² − 9 = (2x + 3)(2x − 3)
16x² − 1 is the difference of squares. This is because 16x² is a perfect square, as is 1. To find the factors of the difference of squares, take the square root of each square; one factor will be the sum of these and the other will be the difference.
The square root of 16x² is 4x and the square root of 1 is 1; this gives us (4x-1)(4x+1).
16x² − 4 is also the difference of squares. The difference of 16x² is 4x and the square root of 4 is 2; this gives us (4x-2)(4x+2). However, we can also factor a 2 out of each of these binomials; this gives us
2(2x-1)(2)(2x+1) = 2(2)(2x-1)(2x+1) = 4(2x-1)(2x+1)
4x² − 1 is also the difference of squares. The square root of 4x² is 2x and the square root of 1 is 1; this gives us (2x-1)(2x+1).
4x² − 9 is also the difference of squares. The square root of 4x² is 2x and the square root of 9 is 3; this gives us (2x-3)(2x+3).
The answer to the question is d
Answer:
m∠A = 31
b = 13.3
Step-by-step explanation:
3, 6, 9, 12,15, 18, 21, 24
8, 16, 24
Marco will fill up his car with gas and wash it on the 24th day.